A hybrid receptor binding protein enables phage F341 infection of Campylobacter by binding to flagella and lipooligosaccharides - Ostenfeld, Line Jensen; Sørensen, Anders Nørgaard; Neve, Horst; Vitt, Amira; Klumpp, Jochen; Sørensen, Martine Camilla Holst (Frontiers in Microbiology, 2024)
Flagellotropic bacteriophages are interesting candidates as therapeutics against pathogenic bacteria dependent on flagellar motility for colonization and causing disease. Yet, phage resistance other than loss of motility has been scarcely studied. Here we developed a soft agar assay to study flagellotropic phage F341 resistance in motile Campylobacter jejuni. We found that phage adsorption was prevented Feltkode aendret by diverse genetic mutations in the lipooligosaccharides forming the secondary receptor of phage F341. Genome sequencing showed phage F341 belongs to the Fletchervirus genus otherwise comprising capsular-dependent C. jejuni phages. Interestingly, phage F341 encodes a hybrid receptor binding protein (RBP) predicted as a short tail fiber showing partial similarity to RBP1 encoded by capsulardependent Fletchervirus, but with a receptor binding domain similar to tail fiber protein H of C. jejuni CJIE1 prophages. Thus, C. jejuni prophages may represent a genetic pool from where lytic Fletchervirus phages can acquire new traits like recognition of new receptors. 2015). Several studies propose that when flagellotropic phages reach the bacterial body they interact with a secondary receptor, where injection of the phage genome takes place (Bender et al., 1989;